Improving The Vocabulary Achievement Of The Seventh Grade Students Of Mts.N 1 Sidenreng Rappang By Using Movie - Yuliana Yuliana (La Ogi : English Language Journal, 2023)
The objectives of this research were to find out: (1) whether or not the use of movie is effective in improving the vocabulary achievement of the Seventh grade students of MTs.N 1 Sidenreng Rappang. And (2) whether or not the Seventh grade students of MTs.N 1 Sidenreng Rappang are interested in improving the vocabulary achievement though movie This research applied pre-experimental method. The subjects of the research were the seventh grade students. There were 30 students. The sampling technique in this research was simple random sampling. The data of this reseach were collected by using two kinds of instruments, namely vocabulary test and questionnare. The result of data analsis showed that there was significant difference between the students’ score in pretest and posttest. It was proven by the mean score of posttest which was higher than pretest (66,8> 37,5). The researcher analyzed the students’ vocabulary achievement through SPSS Version 17.0. Then, the researcher analyzed the students’ interest through SPSS and Likerd Scale. The analysis indicated that the students were strongly interested to improve the vocabulary achievement through movie. It was proved by interest mean (84.76 %) where 53% students were strongly interested and 47% students were interested. Based on the data analysis, the researcher concluded that : (1) the use of movie improves students’ vocabulary achievement; (2) the use of movie makes the students interested in improving vocabulary.